Design and fabrication of mechanical floor cleaner / Muhamad Arif Jailan and Miqdad Khairulmaini - Jailan, Muhamad Arif; Khairulmaini, Miqdad (School of Mechanical Engineering, 2023)
The problem statement addressed in this project is the physical strain and pain experienced by small cleaning contractors, particularly in school cleaning companies, from prolonged use of conventional mops. Additionally, these contractors are faced with the challenge of cleaning large areas such as halls and sports courts, which require an expensive floor scrubber that is not feasible for small cleaning contractors. The main objective of this project is to develop a cost-effective floor cleaner that can replace conventional mops and work similarly to existing floor scrubbers. The methodology employed involves the adaptation of the machine floor scrubber concept to a trolley-based design, which is portable and easy to maneuver. The result of this project is a floor cleaner that is both effective and affordable for small cleaning contractors, particularly in school cleaning companies, to use in cleaning large areas with less physical strain and pain. The significance of this product lies in its potential to provide a practical and economical solution to small cleaning contractors, reducing their burden and improving their working conditions. This product can be marketed as a low-cost alternative to existing floor scrubbers, thereby addressing the challenges faced by small cleaning contractors in maintaining large areas such as schools, sports courts, and halls